PERBEDAAN PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN (SAP) BERBASIS AKRUAL BERDASARKAN TINGKAT PENDIDIKAN, PENGALAMAN KERJA, PELATIHAN, DAN JABATAN (Studi Empiris Pemerintah Kota Jayapura) - Ari Ardianti; Agustinus Salle; Mariolin Sanggenafa (Jurnal Akuntansi dan Keuangan Daerah, 2018)
The Indonesian government had improved the financial bureaucracy to achieve good governance. The method is to adopt a Government Accounting Standards (SAP) of accrual basic. Accrual accounting is believed can produce financial statements more reliable, accurate, comprehensive, and relevant to decision making of economic, social, and political. The purpose of this research is to analyze differences of understanding about Government Accounting Standards accrual basic by the level of education, work experience, training, and occupation. The population of this research are all employees of official government in the local government office of Jayapura Regency. The samples were attained through a purposive sampling method with 84 people/employee from accounting department as respondents. The method of data analyisis is Anova One Way and an independent sample t-test. The test results show that there are different understandings of Government Accounting Standards (SAP) accrual basic of financial employee based on the level of education, work experience, training, and occupation. The different understanding of Government Accounting Standards (SAP) accrual basic between employees graduated from Senior High School and Bachelor are not significant, while there is a significant effect between Senior High School and Undergraduate degree, then the Senior High School and postgraduate indicate insignificant effect, similar with the relation between Bachelor and Undergraduated are not significant, also Bachelor and Postgraduated are not significant, while the Undergraduated and Postgraduated are also not significant. The different understanding of Government Accounting Standards (SAP) accrual basic between employees who have work experience 1-5 years and 6-10 years are not significant, while 1Â5 years and 11-15 years are significant, between 1-5 years and >15 years are significant, 6-10 years and 11-15 years are not significant, 6-10 years and >15 years are not significant, 11-15 years and >15 years are not significant. The different understanding of Government Accounting Standards (SAP) accrual basic between employees who had trained and never trained are significant. The different understanding of SAP accrual basic between employees who had occupation as arranger of the financial statements and in the other job description are significant. The conclusion of this research is that understandings of SAP accrual basic of financial employees can be distinguished based on the level of education, work experience, training, and occupation. Therefore, human resources must be managed with consideration of individual factors to enhance the performance and understanding of SAP accrual basic offinancial employee.